The EU and its neighbours: A second chance to marry democratisation and stability - Kai-Olaf Lang; Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2012)
Times are changing. While the EU's neighbours in the South are on the move, the East is stagnating or rolling back. The EU is reconsidering its strategy and policy towards its neighbours and is trying to make a second attempt to marry democratisation and stability in the South and East. The point of departure is a revision and update of the European Neighbourhood Policy
Keywords: 320